2019
DOI: 10.1108/ijesm-10-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Model risk regarding monthly wind energy production for the valuation of a wind farm investment

Abstract: Purpose The purpose of this paper is to assess model risk with regard to wind energy output in monthly cash flow models for the purpose of valuation and risk assessment of wind farm investments, where only a few approaches exist in the literature. Design/methodology/approach This paper focuses on the risk-return characteristics of this investment from the perspective of private and institutional investors and takes into account several risks, in particular the resource risk related to the uncertainty of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…They concluded that as the inflation rate increases, the return on investment decreases such that this risk should be managed effectively. In agreement with this study, Krömer [10] created a model for the risks involved in wind energy production. For this purpose, Monte Carlo simulation methodology was used.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…They concluded that as the inflation rate increases, the return on investment decreases such that this risk should be managed effectively. In agreement with this study, Krömer [10] created a model for the risks involved in wind energy production. For this purpose, Monte Carlo simulation methodology was used.…”
Section: Discussionmentioning
confidence: 62%
“…The initial cost of these projects is very high. Therefore, the project can become even more costly when inflation increases [10]. Costs incurred during the distribution of all products purchased and electricity generated as a result of wind energy will increase in a high-inflation environment.…”
Section: Literature On the Risk Factors Of Wind Energy Investmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used to broadly refers to firms' ability to understand customer's complex and diverse needs by using its tangible and intangible resources to achieve strong brand recognition (Qureshi, Aziz and Mian, 2017;Lee and Sok, 2017;Al-Mutairi et al, 2018;dos Santos and Marinho, 2018). New products and services development through the differentiation strategy further facilitate SMEs competitive strategy (O'Cass and Sok., 2013;Vinayak &Kodali, 2014;Gatzert and Kosub, 2017;Krömer and Gatzert, 2018;Krömer, 2019). The RBV regards marketing capabilities as part of the imitable corporate organizational resources that form strong component of IJESM 18,1 sustainable competitive advantage (Kozlenkova et al, 2014).…”
Section: Marketing Capabilitymentioning
confidence: 99%